Odpowiedzi

Najlepsza Odpowiedź!
2010-02-02T16:13:39+01:00
A)2x-3y=7/*(-3)
3x-5y=11/*2

-6x+9y=-21
6x-10y=22
------------------
-y=1
y=-1

2x-3y=7
y=-1

2x-3(-1)=7
y=-1

2x=7-3
y=-1

x=2
y=-1
b){5p-2r=21/*3
{3p-5p=-3/*(-5)

{15p-6r=63
+{-15p+25r=30
_____________
19r=93/19
r=4,89
5p-2*4,89=21
r = 4,89

5p=21+9,78
r=4,89

5p=30,78/:5
r=4,89

p=6,15
r=4,89
c)2x-3y=10
5x+5y=0

2x-3y=10
5x=-5y :5

2x-3y=10
x=-y

2(-y)-3y=10
x=-y

-2y-3y=10
x=-y

-5y=10:(-5)
x=-y

y=-2
x=-y

y=-2
x=-(-2)

y=-2
x=2

d)4x + 5y = 12,3 /*3
3x - 2y = -4 /*(-4)

12x+15y=36,9
-12x+8y=16
___________
23y=52,9 //23
y=2,3

4x + 5y = 12,3 /*2
3x - 2y = -4 /*5

8x+10y=24,6
15x-10y=-20
_____________
23x= 4,6 / /23
x=0,3
y=2,3
e)3x-0,2y=35
2,5x-5y=5

3x-0,2y=35
2,5x= 5+5y /:2,5

3x-0,2y=35
x= 2 + 2y

3(2+2y) - 0,2y = 35
x= 2 + 2y

6+6y-0,2y=35
x= 2 + 2y

5,8y=29/:5,8
x= 2+2y

y=5
x=2+10=12
1 4 1
2010-02-02T16:27:14+01:00
A)2x-3y=7/ x 3
3x-5y=11/ x (-2)
6x-9y=21
-6x+10y=-22
y=1

b) 5p-2r=21 /x 3
3p+5r= -6 /x(-5)
15p-6r=63
-15p-25r=30
-31r=93
r=93:(-31)
r=3

c) 2x-3y=10/ x 5
5x+5y=0 / (-2)
10x-15y=50
-10x-10y=0
-25y=50
y=50:(-25)
y=-2

d) 4x+5y=12,3 / x 3
3x-2y=-4 / x (-4)
12x+15y=36,9
-12x+8y=16
23y=52,9
y=52,9:23
y=2,3

e) 3x-0,2y=35 / x (-25)
2,5x-5y=5
-75x+5y=-875
2,5x-5y=5
-72,5x=-870
x=-870:(-72,5)
x=12
2010-02-02T16:29:07+01:00
A) 2x-3y=7/*(-3)
3x-5y=11/*2

-6x+9y=-21
6x-10y=22

-y=1/:(-1)
y=-1

2x-3*(-1)=7
2x+3=7/-3
2x=4/:2
x=2
y=-1

b)5p-2r=21/*5
3p+5r=-6/*2

25p-10r=105
6p+10r=-12

31p=93/:31
p=3

5p-2r=21
15-2r=21/-15
-2r=6/:(-2)
r=-3
p=3

c)2x-3y=10/*5
5x+5y=0/*3

10x-15y=50
15x+15y=3

25x=53/:25
x=2,12

2x-3y=10
4,24-3y=10/-4,24
-3y=5,76/:-3
y=-1,92